Dabigatran etexilate retards the initiation and progression of atherosclerotic lesions and inhibits the expression of oncostatin M in apolipoprotein E-deficient mice - Preusch, Michael; Ieronimakis, Nicholas; Wijelath, Errol S; Cabbage, Sara; Ricks, Jerry; Bea, Florian; Reyes, Morayma; van Ryn, Joanne; Rosenfeld, Michael E (Drug design, development and therapy, 2015)
Objective - Thrombin has multiple proatherogenic effects including platelet activation and the induction of inflammatory processes. Recently, the cytokine oncostatin M has been shown to have proinflammatory effects. This study was designed to investigate the effects of thrombin inhibition on the initiation and progression of atherosclerosis and on the expression of oncostatin M. - - Methods - Apolipoprotein E-deficient mice at different ages were fed the thrombin inhibitor dabigatran etexilate. The mean lesion area was measured in the aortic sinus and in the innominate artery. CD45-positive cells within the aortic tissue were measured by flow cytometry. Oncostatin M expression was measured in the tissue sections by immunocytochemistry. - - Results - Treatment with dabigatran etexilate resulted in a significant reduction of the mean area of atherosclerotic lesions in the aortic sinus in both the young mice (11,176±1,500 μm2 (control) versus 3,822±836 μm2 (dabigatran etexilate), P<0.05) and selectively in the older mice at 28 weeks (234,099±13,500 μm2 (control) versus 175,226±16,132 μm2 (dabigatran etexilate), P<0.05). There were also fewer CD45-positive cells within the aortas of the dabigatran-treated mice and enhanced NO production in endothelial cells pretreated with dabigatran. In addition, the expression of oncostatin M was reduced in the lesions of dabigatran etexilate-treated mice. - - Conclusion - Inhibition of thrombin by dabigatran retards the development of early lesions and the progression of some established lesions in ApoE-/- mice. It improves endothelial function and retards macrophage accumulation within the vascular wall. Dabigatran also inhibits the expression of oncostatin M, and this suggests that oncostatin M may play a role in the initiation and progression of atherosclerosis.
Gesehen am 15.07.2020